Anterior Inter-hemispheric Transcallosal Approach for Resection of Colloid Cyst: A Video Abstract - Sarah Basindwah; Aysha Hawsawi; Amjad Alduhaish; Abdulrazag Ajlan (Indian Journal of Neurosurgery)
Background Although histologically benign, colloid cysts have been an entity of interest to neurosurgeons due to the wide array of possible presentations ranging from asymptomatic to high ICP symptoms to sudden death. It is estimated that colloid cysts represent 0.3 to 2% of all brain tumors.1